The methods and systems of Fault-Tolerant frequency vector control of induction motors in case of the stator circuit damage - Andrii Kalinov; Viacheslav Melnykov; Mohamed Zaidan Qawaqzeh; Mykhaylo Zagirnyak; Artur Szczęsny; Ewa Korzeniewska (International Journal of Electrical Power & Energy Systems)
The paper deals with methods and systems of fault-tolerant control of three-phase induction motors that can be used in regulated drive systems with frequency vector control. The presented methods and systems are designed to maintain the operability and correct the operating modes of a variable-frequency electric drive with minor defects or damage to the stator windings of an electric motor at the early stages of their development, i.e. when the motor operates in an asymmetric mode without actuating the current protection. Such operating modes usually result from inter-turn short circuits or breaks in parallel branches and elementary conductors of phase windings, which are a consequence of insulation breakdown and the occurrence of turn short circuits. In the proposed control systems, the stator voltage is created taking into account additional variable components introduced into the closed control circuits. This voltage form makes it possible to compensate for the induction motor asymmetry caused by damage. Verification of the proposed solutions showed the possibility of maintaining the operability and improving the dynamic characteristics of the damaged electric motor by reducing the additional variable component of the electromagnetic torque. The paper also considers the issue of compensating for the impact of damage to the motor stator windings on the operating modes of the semiconductor elements of the energy converter. The conducted research has shown the possibility of reducing the thermal overload of the motor windings and individual semiconductor elements of the frequency converter, which allows extending their service life. The presented fault-tolerant control methods do not require changes to the hardware of industrial samples of existing variable-frequency electric drives and can be used as additional software blocks.